Pharmacological inhibition of the NLRP3 inflammasome reduces blood pressure, renal damage, and dysfunction in salt-sensitive hypertension. Issue 4 (24th October 2018) - Krishnan, Shalini M; Ling, Yeong H; Huuskes, Brooke M; Ferens, Dorota M; Saini, Narbada; Chan, Christopher T; Diep, Henry; Kett, Michelle M; Samuel, Chrishan S; Kemp-Harper, Barbara K; Robertson, Avril A B; Cooper, Matthew A; et al.
Abstract: Aims: Renal inflammation, leading to fibrosis and impaired function is a major contributor to the development of hypertension. The NLRP3 inflammasome mediates inflammation in several chronic diseases by processing the cytokines pro-interleukin (IL)-1β and pro-IL-18. In this study, we investigated whether MCC950, a recently-identified inhibitor of NLRP3 activity, reduces blood pressure (BP), renal inflammation, fibrosis and dysfunction in mice with established hypertension. Methods and results: C57BL6/J mice were made hypertensive by uninephrectomy and treatment with deoxycorticosterone acetate (2.4 mg/day, s.c. ) and 0.9% NaCl in the drinking water (1K/DOCA/salt). Normotensive controls were uninephrectomized and received normal drinking water. Ten days later, mice were treated with MCC950 (10 mg/kg/day, s.c. ) or vehicle (saline, s.c. ) for up to 25 days. BP was monitored by tail-cuff or radiotelemetry; renal function by biochemical analysis of 24-h urine collections; and kidney inflammation/pathology was assessed by real-time PCR for inflammatory gene expression, flow cytometry for leucocyte influx, and Picrosirius red histology for collagen. Over the 10 days post-surgery, 1K/DOCA/salt-treated mice became hypertensive, developed impaired renal function, and displayed elevated renal levels of inflammatory markers, collagen and immune cells. MCC950 treatment from day 10 attenuated 1K/DOCA/salt-induced increases in renal expression of inflammasome subunits (NLRP3, ASC, pro-caspase-1) and inflammatory/injury markers (pro-IL-18, pro-IL-1β, IL-17A, TNF-α, osteopontin, ICAM-1, VCAM-1, CCL2, vimentin), each by 25–40%. MCC950 reduced interstitial collagen and accumulation of certain leucocyte subsets in kidneys of 1K/DOCA/salt-treated mice, including CD206 + (M2-like) macrophages and interferon-gamma-producing T cells. Finally, MCC950 partially reversed 1K/DOCA/salt-induced elevations in BP, urine output, osmolality, [Na + ], and albuminuria (each by 20–25%). None of the above parameters were altered by MCC950 in normotensive mice. Conclusion: MCC950 was effective at reducing BP and limiting renal inflammation, fibrosis and dysfunction in mice with established hypertension. This study provides proof-of-concept that pharmacological inhibition of the NLRP3 inflammasome is a viable anti-hypertensive strategy.